(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2018)
The treatment of infections caused by resistant microorganisms is limited, and vancomycin (VAN) treatment failures for methicillin-resistant Staphylococcus aureus (MRSA) bacteremia are not uncommon, even when MRSA clinical isolates are susceptible to VAN. Thus, this study proposed the association of VAN with usnic acid and β-lapachone encapsulated into liposomes as a novel therapeutic option for infections caused by MRSA. Liposomes containing β-lap (β-lap-lipo) or usnic acid (UA-lipo) were prepared by the thin lipid film hydration method followed by sonication. Antimicrobial activity against MRSA clinical isolates was investigated by the microdilution method according to the Clinical and Laboratory Standards Institute (CLSI). The interaction studies were carried out using the checkerboard method and epsilometer test (Etest). The interaction between VAN and β-lap or β-lap-lipo was synergistic (FICI = 0.453 and FICI = 0.358, respectively). An additive interaction between VAN and UA (FICI = 0.515) was found. UA-lipo resulted in synergism with VAN (FICI = 0.276). The Etest reproduced the results obtained by the checkerboard method for approximately 82% of the analysis. Thus, the present study demonstrated that VAN in combination with UA-lipo, β-lap or β-lap-lipo synergistically enhanced antibacterial activity against MRSA.